Water Use Efficiency in Rice Cultivar Inpago 7 in The Context of Searching for Drought Tolerant for Indonesia’s National Food Security - Sihombing, Okta Dwi Ellisia; Ramadhan, Daffa Putra; Fendiyanto, Miftahul Huda (MUNISI: Military Mathematics and Natural Sciences, 2025)
Rice is a staple food source in Indonesia, but its production is declining due to drought stress that can hinder its growth and development. Therefore, it is necessary to identify rice varieties resistant to drought stress. This research aims to determine the efficiency of water use in the Inpago 7 rice cultivar. This research uses the method of measuring relative water content. The measurement of relative water content is done by weighing the fresh weight, turgid weight, and dry weight. The samples used are the leaves of the Inpago 7 rice cultivar and Inpago 5 rice cultivar as a positive control, with each sample undergoing two repetitions. Each leaf sample is weighed to obtain the fresh weight, and then distilled water is added and left at room temperature for 24 hours. The leaves are weighed again to obtain the turgid weight. The leaves were dried at a temperature of 60°C for 24 hours, and then the dry weight was measured. The data obtained is then correlated with the physiological responses of the leaves from each sample. The relative water content in the Inpago 5 rice cultivar is lower than the relative water content in the Inpago 7 rice cultivar and has a negative correlation with the physiological response of the leaves. The efficiency of water use in the Inpago 7 rice cultivar can be a candidate for a plant breeding program that is resistant to drought stress, which can support Indonesia's national food security.